A Study on the Detour Self-Decomposition of Corona Product of Graphs - Anlin Bena. E; Merly, E. Ebin Raja (Mathematics and Computer Science: Contemporary Developments Vol. 10, 2024)
A graph G is said to have a detour self-decomposition II = (G1, G2, ..., Gn) if every subgraph Gi, 1 \(\le\) i \(\le\) n of G have the same detour number as the graph G. Detour self-decomposition number of a graph G as the maximum cardinality of the detour self-decomposition II and is represented by the \(π\)sdn (G). Detour self-decomposition on corona product of various graphs and the bounds of detour self-decomposition number are studied in this work.